Three-body bound states in antiferromagnetic spin ladders - Gary Schmiedinghoff; Leanna Müller; Umesh Kumar; Götz S. Uhrig; Benedikt Fauseweh (Communications Physics, 2022)
Most bound quantum states in condensed matter systems emerge due to two-body interactions. Here, the formation of a stable three-particle bound state, induced by irreducible three-particle interactions in an antiferromagnetic spin ladder, is evidenced analytically and numerically for realistic material parameters.